Implementasi Algoritma Random Number Generator Game Edukasi Adventure Pengenalan Istilah Teknologi Informatika - Muhammad Hadid Alfiin; Abdul Jabbar Lubis; Sarudin (LKP KARYA PRIMA KURSUS, 2025)
Implementation of the Random Number Generator Algorithm in Educational Adventure Games Introduction to the Term Information Technology is a research or project that combines computer technology with educational learning through the use of the Random Number Generator algorithm. This research aims to provide an interactive and educational gaming experience to users, especially in the context of understanding information technology terms. In this project, the Random Number Generator algorithm is used to generate random elements in educational games. The main goal is to introduce important terms in the world of information technology to players while providing an entertaining gaming experience. Through this game, users are expected to be able to understand and remember these terms better, while still enjoying the interactive learning process. The results of the test carried out by distributing questionnaires to 15 respondents in total from 5 questions, 0 answered strongly disagree, 0 answered disagree, 15.8% answered doubtfully, 57.9% answered agree, and respondents who answered strongly agreed overall were 26.3% of the games that had been created.